(3GddaX GdQGFb aj ehdO NjQ GdNdGFbs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GUWai ef YHGOg ef TGA hGNJGQ hbOeg Ydi eNdhbGJg ai LejY GdCbWGQ s
(3BNQgG (B:s
(3hGZaQ dcd GdLeY eGbOLfhG cPG PfhH GdeSdejf CLeYjf Je GddaX GdQGFb ai ehdO NjQ GdNdGFb s
(3cJHJ HNW eged GdfbW CMjGfkGs
(3Ydi MGTjI fSNJfG gPg SeGY HNW GdeDda hHBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg TgO G deDda Ydi gPG GdSeGY hELGRI HNWgs
(3HgG fXGe GdJYbjHIs
(3hUaMI GdZdGa CjVkG HNW GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdeLGejYs